The Little-known Freshwater Metopid Ciliate, Idiometopus turbo (Dragesco and Dragesco-Kernéis, 1986) nov. gen., nov. comb., Originally Discovered in Africa, Found on the Micronesian Island of Guam - Bourland, William; Rotterová, Johana; Luo, Xiaotian; Čepička, Ivan (Protist, 2018)
Class Armophorea Lynn, 2004 includes two orders of mainly free-living anaerobic ciliates, Armophorida Jankowski, 1980 and Metopida Jankowski, 1980 and, a third, the exclusively endosymbiotic Clevelandellida. Kahl described the majority of free-living metopid species early in the 20th century. Excepting Jankowski in the 1960's, little further interest was shown in this group. Metopus turbo Dragesco and Dragesco-Kernéis, 1986, from a West African pond, was more recently described. Although not explicitly described as endemic, Dragesco believed in some degree of endemism of sub-Saharan ciliates. Our discovery of M. turbo on Guam, Micronesia was unexpected. Metopus turbo was identified by live observation, protargol impregnation, and scanning electron microscopy, providing reasonable evidence of conspecificity when compared with the original description. Outstanding morphologic features include the stout shape and transversely situated bandform macronucleus. The morphology of Metopus turbo differs markedly from that of the Metopus/Brachonella clade and is distant from Metopus es in phylogenetic analyses. The 18S rDNA sequence of the Guam M. turbo differs from that of M. es, type species of Metopus, by >8% and shows distinct morphologic differences from the genus Atopospira to which it is sister. These facts suggest that transfer to a new genus, Idiometopus gen. nov. is indicated.
Keywords: Guam; molekulární typizace; sladká voda; Ciliophora; Africa; Molecular Typing; phylogeny; Fresh Water; Afrika; Phylogeny; Armophorea; fylogeneze; anaerobic ciliates; protargol; Metopida; 18S rRNA gene.